A research agenda for nonvascular photoautotrophs under climate change. Issue 5 (13th December 2022) - Porada, Philipp; Bader, Maaike Y.; Berdugo, Monica B.; Colesie, Claudia; Ellis, Christopher J.; Giordani, Paolo; Herzschuh, Ulrike; Ma, Yunyao; Launiainen, Samuli; Nascimbene, Juri; Petersen, Imke; Raggio Quílez, José; et al.
Summary: Nonvascular photoautotrophs (NVP), including bryophytes, lichens, terrestrial algae, and cyanobacteria, are increasingly recognized as being essential to ecosystem functioning in many regions of the world. Current research suggests that climate change may pose a substantial threat to NVP, but the extent to which this will affect the associated ecosystem functions and services is highly uncertain. Here, we propose a research agenda to address this urgent question, focusing on physiological and ecological processes that link NVP to ecosystem functions while also taking into account the substantial taxonomic diversity across multiple ecosystem types. Accordingly, we developed a new categorization scheme, based on microclimatic gradients, which simplifies the high physiological and morphological diversity of NVP and world‐wide distribution with respect to several broad habitat types. We found that habitat‐specific ecosystem functions of NVP will likely be substantially affected by climate change, and more quantitative process understanding is required on: (1) potential for acclimation; (2) response to elevated CO2 ; (3) role of the microbiome; and (4) feedback to (micro)climate. We suggest an integrative approach of innovative, multimethod laboratory and field experiments and ecophysiological modelling, for which sustained scientific collaboration on NVP research will be essential.